2021
DOI: 10.58258/jisip.v5i3.2228
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Covid-19 Terhadap Perekonomian Di Negara Asean

Abstract: Penelitian ini bertujuan untuk menguji pengaruh covid-19 terhadap perekonomian di negara ASEAN. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan menggunakan data sekunder berupa jurnal ilmiah dan studi literatur lainnya. Berdasarkan hasil penelitian, penulis dapat menyimpulkan bahwa dampak dari pandemi virus corona tidak hanya pada sektor kesehatan, tetapi semua sektor juga merasakan dampaknya. Salah satunya, sektor ekonomi dan bisnis. Pertumbuhan ekonomi global dipastikan mengalami k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Tetteh et al (2022) report that the case reports including the death rate from Covid-19 had a negative impact on the performance of financial markets in Ghana and Botswana from March 1, 2020, to September 30, 2021. At the ASEAN level, some studies from Dewi et al (2021), Octavera and Rahadi (2021), and Romadhon and Ardiansyah (2022) report that capital market conditions have worsened due to the Covid-19 pandemic. Some studies as found by Putri (2020), Nasution et al (2020), Sumarni (2020), Aeni (2021), Hamzah et al (2021), and Akhmad (2022) also report the adverse impact of Covid-19 on the economy and especially the capital market in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Tetteh et al (2022) report that the case reports including the death rate from Covid-19 had a negative impact on the performance of financial markets in Ghana and Botswana from March 1, 2020, to September 30, 2021. At the ASEAN level, some studies from Dewi et al (2021), Octavera and Rahadi (2021), and Romadhon and Ardiansyah (2022) report that capital market conditions have worsened due to the Covid-19 pandemic. Some studies as found by Putri (2020), Nasution et al (2020), Sumarni (2020), Aeni (2021), Hamzah et al (2021), and Akhmad (2022) also report the adverse impact of Covid-19 on the economy and especially the capital market in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the COVID-19 pandemic has raised several problems for MSME and cooperative actors, on the other hand opportunities have also arisen (Dewi, et al, 2021). 6.…”
Section: Introductionmentioning
confidence: 99%
“…From an economic point of view, it is essential to seek new supply chain management strategies to survive in today's competitive and changing business environment (Yu, Jacobs, Chavez, & Yang, 2019). As a result of the Covid-19 pandemic, people's purchasing power in the mall sector and mall finance has decreased (Dewi, Aulia, Sumunar, & Hernawati, 2021). The availability of technology affects the availability and speed of internet connections which greatly benefits employees as several companies and governments implement work-from-home (WFH) schemes that allow more flexibility in scheduling employee working hours without losing work time (Kelly et al, 2022).…”
Section: Introductionmentioning
confidence: 99%